Philosophy as a ‘resistance identity’? Dialogue on modernist philosophical difference with Taha Abdul Rahman - George Awad, Najib (Münster journal for Islamic and philosophical studies, 2022)
This study aims to examine the philosopher Taha Abdurrahman’s thesis on the formation of a contemporary Arab modernist philosophy that declares the explicit epistemological right to model‭ ‬an Arab-philosophical identity in contrast with and differentiation from European philosophy‭. ‬I will first present a systematic‭ ‬and descriptive presentation of Taha Abdurrahman's thesis in his book al-Haq al-arabi fi al-ikhtilaf al-falsafi‭ (‬The Arab Right‭ ‬to Philosophical Difference‭). ‬Then I will present a critical and dialogical deconstruction of his thesis through a dialogue between it and epistemological propositions related to the same orientation and epistemological concerns that I find in Fathi al-Miskini’s philosophical approaches to identity and the self in his book al-huwiyah wa-al-huriyah‭: ‬nahwa anwar jadida‭ (‬Identity and Freedom‭: ‬Towards a new enlightenment‭), ‬as well as Aziz al-Azmeh’s historical approaches related to the study of Islamic thought as a historical phenomenon‭, ‬especially in his last book The Emergence of Islam in Late Antiquity‭.‬